Research on Components Assembly Platform of Biological Sequences Alignment Algorithm - Shi, Haihe; Wu, Gang; Zhang, Xuchu; Wang, Jun; Shi, Haipeng; Xu, Shenghua (Frontiers in Genetics, 2021)
After years of development, the complexity of the biological sequence alignment algorithm is gradually increasing, and the lack of high abstract level domain research leads to the complexity of its algorithm development and improvement. By applying the idea of software components to the design and development of algorithms, the development efficiency and reliability of biological sequence alignment algorithms can be effectively improved. The component assembly platform applies related assembly technology, which simplifies the operation difficulty of component assembly and facilitates the maintenance and optimization of the algorithm. At the same time, a friendly visual interface is used to intuitively complete the assembly of algorithm components, and an executable sequence alignment algorithm program is obtained, which can directly carry out alignment computing.